IMPLEMENTASI P5 (PROJEK PENGUATAN PROFIL PELAJAR PANCASILA) PADA KURIKULUM MERDEKA BELAJAR DALAM PEMBELAJARAN ILMU PENGETAHUAN ALAM - Safitri, Rida Echa; Rahim, Abdul (Balai Besar Guru Penggerak Jawa Timur, 2023)
In the academic year 2022/2023, the Indonesian government ratified and commenced the implementation of a new curriculum resulting from the refinement of the previous curriculum, namely the